CONTEMPORARY UNIVERSITY: FROM THEORY TO KNOWLEDGEFACTORY - Dimitrovski, Robert; Blazevski, Ivan; Spahiu, Isa; Mirchevska, Elena; Jovevska, Dijana; Pushova, Liljana; Doneva, Elena (European Scientific Journal, ESJ, 2014)
Elevation of technological innovations, achievements generating permanent development, globalization and universal connection had determined other types of level and knowledge criteria for current and especially future workers. Number of university educated workers is expected to be rapidly raised up on behalf of the high school educated workers. As last third level of education, the university education profiles the future workforce. Correspondingly, the character meaning yet more insists on knowledge that apart from theoretical values will also have practical – being enforceable. According to Peter Senge, the new knowledge expensive seeds do not always fall on rich ground. The university institutions yet more oriented from clearly theoretical-narrative and transfer knowledge poured off to creative-pragmatic. The direction of transmitted examination is yet more imperative. The university institutions manifest their function in different ways with same focus, but different results.